An Ecological Perspective on Youth Career Education in Transitioning Societies: China as an Example. (December 2019) - Xie, Dong; Kong, Ning; Skaggs, Sydney; Yang, Anbo
Contextual factors have received increased attention in understanding the challenges and difficulties in translating career education and career guidance services from Western societies to non-Western societies, many of which are undertaking a shift from a socialist and collectivistic system to a more individualistic one. In this article, using China as an example, we discussed the contextual factors in different ecological systems, such as economical, educational, and sociocultural, and how they may facilitate or impede youth career education in a transitioning society. We reviewed a career education program in a Chinese senior middle school to illustrate such impacts. Additionally, we proposed strategies for further development of youth career education in China as well as in other countries with similar transitions. We introduced a framework of a diversified concept of career and several context-resonant career development theories to be considered in guiding youth career education programs in these transitioning societies.